2020
DOI: 10.1016/j.bbmt.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Third Annual Blood and Marrow Transplant Clinical Trials Network Myeloma Intergroup Workshop on Minimal Residual Disease and Immune Profiling

Abstract: The third annual Blood and Marrow Transplant Clinical Trials Network (BMT CTN) Myeloma Intergroup Workshop on Minimal Residual Disease and Immune Profiling was held on November 29, 2018, at the American Society of Hematology (ASH) annual meeting. This workshop featured the latest research focused on minimal residual disease (MRD) assessment and immune profiling (IP) in myeloma as well as discussion of the statistical and regulatory issues intrinsic to the development of MRD as a surrogate endpoint. In this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…54 Minimal residual disease testing has been developed for MM, and its role is actively being defined for prognostication and treatment decision-making in the induction, transplant, consolidation, and maintenance settings. 55 This technology is in its initial stages of development and application for WM and may help clarify the role for hematopoietic cell transplantation in WM. Identifying optimal timing for stem cell transplantation remains an open question that bears addressing in future studies, as does developing strategies to reduce NRM, notably in allo-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…54 Minimal residual disease testing has been developed for MM, and its role is actively being defined for prognostication and treatment decision-making in the induction, transplant, consolidation, and maintenance settings. 55 This technology is in its initial stages of development and application for WM and may help clarify the role for hematopoietic cell transplantation in WM. Identifying optimal timing for stem cell transplantation remains an open question that bears addressing in future studies, as does developing strategies to reduce NRM, notably in allo-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development and availability of new treatment choices for MM, MM patients will have the opportunity to achieve appreciable treatment responses. The Blood and Marrow Transplant Clinical Trials Network Myeloma Intergroup Workshop (BMT CTN Myeloma Intergroup Workshop) has indicated that MRD detection and immune monitoring are important for MM patients ( 97 99 ). Based on the discussion put forth by our review, we know that certain immune profiling such as ACL and B cell absolute counts can be used for the prediction of prognosis of real-world myeloma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MRD as a sur ro gate end point for reg u la tory pur poses is an area of active dis cus sion 25 and is being addressed by a con sor tium of aca demic groups and phar ma ceu ti cal part ners, the International Independent Team for Endpoint Approval of Myeloma MRD. [26][27][28] The depth of MRD neg a tive sta tus is also impor tant. This was ini tially shown with flow cytom e try with sen si tiv ity down to 10 −4 and where each log reduc tion in MRD trans lated into improvement in median OS.…”
Section: Importance Of Depth Of Responsementioning
confidence: 99%